The functional lumbar index: Validation of a novel clinical assessment tool for individuals with low back pain. (December 2022) - Harris, Sean; Roddey, Toni; Shelton, Tamara; Bailey, Lane; Brewer, Wayne; Ellison, Jennifer; Wang, Wanyi; Gleeson, Peggy
Abstract: Study design: Retrospective Diagnostic Cohort Study. Level of evidence: Level 3b. Objectives: To examine the concurrent and predictive validity of a novel clinical assessment tool, the Functional Lumbar Index (FLI). Background: Lumbar surgeries have increased exponentially in the past decade, adding to healthcare costs without improving outcomes. Limitations in clinicians' abilities to identify those individuals who are most likely to benefit from surgery may be enhanced with an effective physical assessment tool. Methods: The FLI was assessed on 291 individuals (179 conservative and 113 pre-surgical) seeking care for low-back pain (LBP) over a 2.5-year period. The FLI consists of several physical performance tests (PPT) with a novel criterion-based scoring system. Pearson correlations and Poisson regression analysis were used to establish concurrent and predictive validity at alpha = 0.05. Results: The subscale FLI components showed good to excellent inter-rater reliability with intraclass correlation coefficient values as follows: front plank = .993, right side plank = .824, left side plank .861, Sorensen = 0.836, overhead squat = 0.937. A statistically significant, moderate negative correlation was observed between FLI and modified Oswestry Disability Index (r = −0.540, p < .001). Regression analysis showed the FLI as the only significant predictor (p = .004) of failed conservative management for individuals with LBP. An ROC curve showed significant group prediction of the FLI with an AUC of 0.788 (p < .001) and cut-off score of 7.5. Conclusion: The FLI is a reliable and valid measure for predicting failed conservative care management in patients with LBP. Clinicians are encouraged to use the FLI as part of their physical assessment when screening individuals with LBP who might need surgical intervention. Further research is needed to determine validity of the FLI in other patient populations. Public trial registry: N/A. Highlights: Journal of Musculoskeletal Science and Practice Revision Highlights. There are very few valid functional measures for low back pain. The functional lumbar index is both reliable and valid for low back pain. This new tool can be used to better identify those at risk for lumbar surgery.